2013
DOI: 10.1007/s11095-013-1058-8
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Efficacy of R8-Modified Paclitaxel-Loaded Liposomes on Pulmonary Arterial Hypertension

Abstract: In conclusion, the drug delivery system of R8-modified paclitaxel-loaded liposomes we established showed pronounced inhibitory effect over VSMCs proliferation and cytoskeleton formation in vitro, a stronger pulmonary delivery ability in vivo, and was effective on PAH, showing the potential for pulmonary drug delivery system for PAH treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…For example, polyethylene glycol (PEG)ylation has been extensively employed to increase the accumulation of liposomes in tumor tissues via enhanced permeability and retention (EPR) effects (i.e., passive targeting) (11). To increase the specificity of the interactions between liposomes and tumor cells, various studies have focused on the development of active tumor-targeted liposomes modified with specific ligands, including transferrin (12), folic acid (13), peptides (14)(15)(16)(17)(18) or antibodies (19)(20)(21). These modified liposomes are able to selectively recognize and bind to specific receptors overexpressed on tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…For example, polyethylene glycol (PEG)ylation has been extensively employed to increase the accumulation of liposomes in tumor tissues via enhanced permeability and retention (EPR) effects (i.e., passive targeting) (11). To increase the specificity of the interactions between liposomes and tumor cells, various studies have focused on the development of active tumor-targeted liposomes modified with specific ligands, including transferrin (12), folic acid (13), peptides (14)(15)(16)(17)(18) or antibodies (19)(20)(21). These modified liposomes are able to selectively recognize and bind to specific receptors overexpressed on tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…The delivery system of R8-modified liposomes has shown potential as a pulmonary drug delivery system for PAH treatment (25). We modified the lung-specific delivery system using siRNA-loaded liposomes (R8-Lip-siMEG3) and found that the biodistribution of R8-Lip in the lung reached high levels in 1 h, which were maintained for 24 h. Thus, we repeated this application of R8-Lip-siMEG3 during hypoxia treatment.…”
Section: Discussionmentioning
confidence: 99%
“…To silence the expression of lncRNA-MEG3, PASMCs were transfected with the small interfering RNA To knock down the expression of lncRNA-MEG3 in pulmonary arteries (PAs), siRNA against lncRNA-MEG3 (siMEG3) was loaded with octaarginine (R8) conjugated PEG2000-Lipid (R8-Lip) to form a lung-specific delivery system (R8-Lip-siMEG3) as previously described with some modifications. (25) Briefly, octaarginine (R8) and DSPE-PEG2000-Mal (molar ratio: 1.5:1) were mixed in chloroform/methanol (v/v = 2:1) at room temperature with gentle stirring for 48 h. The mixture was evaporated under vacuum and then re-dissolved in chloroform, after discarding the insoluble material; the supernatant (DSPE-PEG2000-R8) was evaporated again under vacuum. Lipid compositions of the prepared liposomes were as follows: R8 modified liposomes (R8-LIP), SPC/Chol/DSPE-PEG2000/DSPE-PEG2000-R8 (molar ratio 59:33:3:5).…”
Section: Lncrna-meg3 Knockdown In Vivo and In Vitromentioning
confidence: 99%
“…A few parts of the lungs from Group M2, in which ATM expression was increased, were used for PA-SMCs isolation and culture. Rat PA-SMCs were isolated and cultured following the protocol previously described by Yin [ 17 ]. Assays were performed at passages 3-5.…”
Section: Methodsmentioning
confidence: 99%